Risk factors and implications associated with renal mineralization in chronic kidney disease in cats. (19th January 2022) - Tang, Pak‐Kan; Jepson, Rosanne E.; Chang, Yu‐Mei; Geddes, Rebecca F.; Hopkinson, Mark; Elliott, Jonathan
Abstract: Background: Nephrocalcinosis is a pathological feature of chronic kidney disease (CKD). Its pathophysiological implications for cats with CKD are unexplored. Objectives: Identify nephrocalcinosis risk factors and evaluate its influence on CKD progression and all‐cause mortality. Animals: Fifty‐one euthyroid client‐owned cats with International Renal Interest Society (IRIS) stages 2‐3 azotemic CKD. Methods: Retrospective cohort study. Histopathological kidney sections were assessed for nephrocalcinosis (von Kossa stain). Nephrocalcinosis severity was determined by image analysis (ImageJ). Ordinal logistic regressions were performed to identify nephrocalcinosis risk factors. The influence of nephrocalcinosis on CKD progression and mortality risk were assessed using linear mixed model and Cox regression, respectively. Cats were categorized by their owner‐reported time‐averaged phosphate‐restricted diet (PRD) intake, where PRD comprised ≥50%, 10‐50%, or none of food intake. Results: Nephrocalcinosis was rated as mild‐to‐severe in 78.4% and absent‐to‐minimal in 21.6% of cases. Higher baseline plasma total calcium concentration (tCa; odds ratio [OR] = 3.07 per 1 mg/dL; P  = .02) and eating a PRD (10%‐50%: OR = 8.35; P  = .01; ≥50%: OR = 5.47; P  = .01) were independent nephrocalcinosis risk factors. Cats with absent‐to‐minimal nephrocalcinosis had increasing plasma creatinine (0.250 ± 0.074 mg/dL/month; P  = .002), urea (5.06 ± 1.82 mg/dL/month; P  = .01), and phosphate (0.233 ± 0.115 mg/dL/month; P  = .05) concentrations over a 1‐year period, and had shorter median survival times than cats with mild‐to‐severe nephrocalcinosis. Conclusion and Clinical Importance: Higher plasma tCa at CKD diagnosis and PRD intake are independently associated with nephrocalcinosis. However, nephrocalcinosis is not associated with rapid CKD progression in cats.